Causes d’examens de suivi au 60ème jour de Paralysie flasque aigue (PFA) en RD Congo ; Cas de la province de la TSHOPO - MANDEFU, Salomon OTOWANGE; Xavier BOGENDA BAILA; Santhos LOBWA BOSONGO; Dieudonné EPELEKA MAZEMBE (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Of January to August 2019, 36 on the 102 cases of sharp Flabby Paralysis (PFA) notified, either 34,2% of the cases were the subject of follow-up exams to the 60ème day to the provincial Division of the health of the Tshopo. Thing that attracted our particular attention. This is how we set like objective to determine the reasons of follow-up exams on the 60th day to be able to contribute to the eradication of the poliomyelitis through a good follow-up and a framing of the land beneficiaries in research and investigating of the cases. We led a descriptive transverse survey in the DPS TSHOPO. She/it concerned 36 cases of the sharp Flabby Paralysis that were the subject of follow-up exams on the day 60 since the date of beginning of the paralysis. Of the analysis of the elements to our range, we observed 100% of exhaustiveness of the follow-up of samples to the 60th days (n=5) in the Lokutu antenna; 72% of samples of two Antenna PEVS had arrived late (> 14 days) to the National laboratory; the average delay between the date of the beginning of the Paralysis and the 2nd withdrawal of samples was of 8 days (E.T ± 5 days); the average of interval of hours between the 2 withdrawals was of 18 hours (E.T. ±24 hours) and 97% of withdrawals made themselves between 24 at 48 o’clock. The conditions of arrival of samples to the National laboratory were bad (100% for the Lokutu antenna); the middle delay of the arrival of samples to the National laboratory was of 9 days (E.T.±8 days) and 57% of samples had arrived in a delay understood between 4 to 7 days, 69% of exams follow-up were negative. So therefore, the rigorous management of samples by all taking parts of the Surveillance of the sharp Flabby Paralysis associated to the formation and information constitutes the remedy to reduce the number of follow-up exams on the day 60.